Community-Based Conservation and Tourism Integration: A Bibliometric and Risk-Based Assessment for Sustainable Management of Ranu Darungan - Asti Amelia Novita; Gita Zulfie Ramadhani (Administratio, 2026)
This study aims to map research trends and strategic risks in sustainable tourism management within conservation areas using bibliometric analysis via VOSviewer and a risk assessment matrix. Based on 137 Scopus-indexed articles, findings reveal that themes such as sustainable tourism, collaborative governance, and conservation have evolved dynamically since 2013, shifting toward integrating governance, ecosystem services, and sustainable development. The six major thematic clusters identified were then translated into locally relevant risk categories through stakeholder-based assessment. The highest-priority risks were visitor overcapacity and habitat disturbance. This research provides an integrated analytical approach that links worldwide governance trends identified by bibliometric mapping with locally specific risk priorities, laying a pragmatic ground for adaptive governance and sustainable tourism management in conservation zones.